High School Students with Digital Era Entrepreneurship Skills: A Basic Training Approach - Premananda, Ni Luh Putu Uttari (LPPM Universitas Jambi, 2023)
This community service initiative aims to equip 10th-grade students of SMAK Santo Yoseph Denpasar with fundamental entrepreneurship knowledge and business pitching skills. The program specifically focuses on training students in business idea creation, branding, promotion, and business ethics. The methodology incorporates both lectures and hands-on practice, with a particular emphasis on the design and development of business ideas. Participants engage in interactive sessions, where they actively create business concepts and refine their pitching presentations. By the end of the training, students successfully generated business ideas and conducted simulated business pitches. The results indicate that students not only gained valuable entrepreneurial skills but also developed the confidence to present their ideas effectively. This activity received positive feedback from participants, highlighting the effectiveness of combining theoretical learning with practical experience in preparing students for entrepreneurship in the digital era.